Does operational disclosure curb textual tone manipulation by corporate management? - Qingxi Meng; Xingqiang Du; Xiaoyun Gong (China Journal of Accounting Studies)
Information disclosure regulations play a crucial role in shaping the information disclosure behaviour of company management, influencing the information environment of capital markets, and subsequently impacting the efficiency of resource allocation. Drawing on a quasi-experimental approach involving the phased implementation of the Industry Information Disclosure Guidelines (IIDG) and utilising data from Chinese listed companies spanning 2010–2021, we delve into the governance effects of the IIDG on company management’s textual tone manipulation and its mechanisms. Our findings reveal a significant reduction in the degree of textual tone manipulation in firm management discussions and analyses following the IIDG implementation. This is achieved through various channels, including enhanced disclosure of quantitative information related to firms’ operations, increased comparability of textual information across firms, and heightened investor attention. The governance effect is more pronounced when management has stronger incentives to manipulate the tone of the text and when there is more room for manipulation. Moreover, the IIDG has a spillover effect, extending to the suppression of tone-of-text manipulation in sections of the annual report beyond the management discussion and analysis. Additionally, investors penalise firms that continue to engage in tone manipulation after the IIDG implementation, as evidenced by a negative market reaction. We not only furnish micro-level evidence regarding the effectiveness of the IIDG as regulatory measures for disclosure but also introduces new perspectives on governing textual tone manipulation.